2020
DOI: 10.3390/cancers12040838
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Molecules On Lung Cancer Stem Cells From Lymph Nodes Aspirates

Abstract: Over the past decade, immune checkpoint inhibitors have revolutionized the treatment of non-small cell lung cancer (NSCLC). Unfortunately, not all patients benefit from PD-(L)1 blockade, yet, the PD-L1 tumor cell expression is the only approved biomarker, and other biomarkers have been investigated. In the present study, we analyzed the presence of immunomodulatory molecules: PD-L1, CD47, CD73, Fas, and FasL on mature tumor cells (MTCs) and cancer stem cells (CSCs) in lymph nodes (LNs) aspirates and refer it t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
0
0
Order By: Relevance
“…Other researchers confirm the presence of effector lymphocytes at the site of the ongoing neoplastic process and their prognostic importance. Our present and former findings indicate specificity of the character of the environment of the metastatic tumor site ( 52 55 ). The high number of CD8+ CD45RO+ effector memory T cells found in the primary tumor lesion significantly correlates with a positive clinical outcome in various cancers.…”
Section: Discussionsupporting
confidence: 72%
“…Other researchers confirm the presence of effector lymphocytes at the site of the ongoing neoplastic process and their prognostic importance. Our present and former findings indicate specificity of the character of the environment of the metastatic tumor site ( 52 55 ). The high number of CD8+ CD45RO+ effector memory T cells found in the primary tumor lesion significantly correlates with a positive clinical outcome in various cancers.…”
Section: Discussionsupporting
confidence: 72%
“…Functionally, CD47 blockade using anti-CD47 or anti-SIRPα mAb significantly increased macrophage phagocytosis of LCSC isolated from NSCLC cell lines and patient tumors. A second study that investigated immunomodulatory molecules in LCSC obtained from lymph node aspirates, confirmed that CD47 expression was higher on cancer stem cells compared to mature tumor cells [241]. These findings may suggest that CD47 has a role in maintaining the stem cell compartment in NSCLC.…”
Section: Cancer Stem Cellsmentioning
confidence: 76%
“…However, observational studies do not indicate any significant differences in PD-L1 expression between men and women [122], which was confirmed in some of our studies. We explored immune cell phenotypes and expression of immune checkpoints of immune cells derived from the blood and TME of lung cancer patients [123]. When analyzing differences between sex, we did not find spectacular results.…”
Section: Estrogens and Tmementioning
confidence: 94%